Parental leave in the Czech Republic and Slovakia: Where is it more favourable to become a father? - Denisa Nevická; Juraj Hamulák; Mikuláš Krippel (DANUBE: Law, Economics and Social Issues Review, 2021)
The article deals with the position of the child's father in labour relations. The comparative analysis of legislation in the Czech Republic and Slovakia is based not only on labour law, but also on social security law and anti-discrimination law. The authors aim to point out the difference in treatment and answer the fundamental research question - In which country is it easier for a man to reconcile work and family responsibilities?
Keywords: 330; Father; Social Security; Employer; Employee; Parental Leave; Discrimination